Comparative Biochemical Study of Glutathione, Ceruloplasmin and Trace Element in Sera of Control Group and Human Female Patients with Osteoarthritis Nodal in Iraqies Patients - Al – Wihaly, B. H. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The present study conducted on 30 female patients with osteoarthritis 0A a attending Baghdad teaching hosp ital, in addition to 30 healthy females , all subjects were ( 35-65) years old. Some biochemical parameters were measured in the sera of patients and healthy group s. The parameters were Glutathione (GSH). Ceruloplasmin (Cp) and some trace elements ,including Copper (Cu) ,Cu/ Cp ratio and Selenium (Se) were determined . The results revealed a significant reduction in all parameters of patients sera compared to healthy group . The reduction in GSH and Cu/Cp ratio confirms tissue damage associated with oxidative stress injury A conclusion was obtained hrer ,that Cu wasn’t an important element in oxidative stress in p atients .